Thermal Ablation Versus Wedge Resection for Stage I Non-small Cell Lung Cancer Based on the Eighth Edition of the TNM Classification: A Population Study of the US SEER Database - Zeng, Chenxi; Lu, Jiawei; Tian, Yitao; Fu, Xiangning (Frontiers in Oncology, 2020)
Background: The incidence rates of early-stage non-small cell lung cancer (NSCLC) are now increasing, and therapies such as thermal ablation have shown potential therapeutic promise. This study aimed to determine the influence of different surgical methods on overall survival (OS) and cancer-specific survival (CSS) in patients with stage I NSCLC. Method: Patients diagnosed with stage I NSCLC receiving thermal ablation or wedge resection between 2004 and 2014 were obtained from the Surveillance, Epidemiology, and End Results (SEER) database. Propensity score matching (PSM) was performed according to the surgical method. Kaplan–Meier curves and Cox proportional hazard model were used to evaluate OS and CSS. Results: In all, 4372 patients with stage I NSCLC were included. Before PSM, the respective 3- and 5-year OS rates were 68.9% and 52.7% in the wedge resection group and 68.5% and 47.8% in the thermal ablation group (p<0.0001); the corresponding CSS rates were 79.1% and 69.4% and 62.6% and 46.0% (p<0.0001). After PSM, survival analysis showed that wedge resection had better OS (44.5% vs. 30.1%, p=0.033) and CSS (63.5% vs. 46%, p=0.038) than thermal ablation. After PSM, Cox regression showed that treatment is not associated with OS or CSS. For patients aged >75 years, thermal ablation showed similar OS and CSS as wedge resection (OS: 30.6% vs. 41.7%, p=0.470; CSS: 46.4% vs. 64.1%, p=0.100). After PSM, thermal ablation still had OS (30.6% vs. 41.0%, p=0.470) and CSS (46.4% vs 59.8%, p=0.100) comparable to wedge resection. Conclusion: For patients with stage I NSCLC who are unfit for lobotomy, thermal ablation could be a potential therapeutic option, especially for those >75 years old.